Optimization of ultrasound pretreatment and enzymatic hydrolysis of wheat straw: From lab to semi-industrial scale. (20th December 2022) - Calcio Gaudino, Emanuela; Grillo, Giorgio; Tabasso, Silvia; Stevanato, Livio; Cravotto, Giancarlo; Marjamaa, Kaisa; Pihlajaniemi, Ville; Koivula, Anu; Aro, Nina; Uusitalo, Jaana; Ropponen, Jarmo; Kuutti, Lauri; et al.
Abstract: In this paper, the dominance of the physical effects of ultrasound (US) pretreatment in improving the delignification of wheat straw at a 1:20 solid/liquid (biomass/water) ratio is reported showing low-frequency/high power (25 kHz, 2 or 3 kW) as preferred conditions. The sonochemical pretreatment with alkali was identified as an optimal method to make the cellulose more susceptible to further enzymatic hydrolysis, thereby increasing the yield of soluble sugars. Previous bench-scale studies have shown that US pretreatment has a positive effect on delignification, nevertheless this has not yet been demonstrated on a larger scale. The objective of this study was to demonstrate the effectiveness of US pretreatment for wheat straw delignification from lab to semi-industrial scale (40 kg biomass) in terms of sugar yield and energy efficiency. A 59.2% of lignin removal was recorded after the cavitational treatment of wheat straw with a subsequent 68 ± 5.7% yield in terms of enzymatic hydrolysis (52.6% glucose, 42.9% xylose and 4.5% arabinose). It was demonstrated that the positive effect of US alkali pretreatment of wheat straw on sugar yield was due to a combination of factors, including (i) an easier accessibility of the biomass carbohydrate network to enzymes due to the increased wheat straw porosity, (ii) the partial removal of lignin, which increases the relative proportion of carbohydrates in the treated biomass, and (iii) the disordering (amorphization) of the cellulose structure, which promotes carbohydrate hydrolysis as well as saponification of the acetyl groups in the hemicellulose. With respect to the Life Cycle Assessment (LCA) and the Cost Benefit Analysis the US pretreatment process herein reported was compared to an alternative Steam Explosion pretreatment. The results of the LCA analysis showed, that for all five environmental categories (energy consumption, global warming potential, water and fossil depletion, and the land occupation) the US pretreatment has advantages in comparison with the standard industrial Steam Explosion pretreatment. Graphical abstract: Image 1 Highlights: Residual biomass as sustainable source for the production of fermentable sugars. Ultrasound as alternative technology for the scalability of biomass conversion. First study on ultrasound pretreatment of wheat straw at semi-industrial scale. First study on enzymatic hydrolysis of pretreated biomass at semi-industrial scale. Life Cycle Assessments of wheat straw valorization at semi-industrial scale.